Pilomatrixoma of the scalp: peculiar presentation possibly related to topography - Suellen Ramos de Oliveira; Thiago Jeunon; Carolina Fechine (Sociedade Brasileira de Dermatologia (SBD), 2023)
Pilomatrixoma is a benign tumor with differentiation to the hair matrix that can affect different regions of the skin. We report the case of a patient with an unusual presentation on the scalp, with warning signs for the possibility of a malignant variant of the tumor. We emphasize the importance of documenting atypical conditions that may permeate the practice of dermatologists and the need to rule out malignancies in the face of a change in the pattern of skin lesions, exulcerations, and bleeding, among other signs. The role of histopathology is fundamental for diagnostic definition and therapeutic management.